Development and storage stability of smoked sailfish (istiophorus platypterus). - Espolong, Raadel Joy C. (College of Fisheries, University of the Philippines, 1993)
The most acceptable process for smoking of Indo-Pacific sailfish was determined b finding out: 1) the effect of brine concentration on acceptability; 2) effect of curing solution on flavor and texture and 3)acceptability of hot and cold smoked fish. Sensory evaluation results showed that products soaked that 60° salinometer brine solution with Monosodium Glutamate and sugar, then subjected to cold smoking was most acceptable. The finished product has a glossy, reddish brown color and soft to tender texture at the center. It has a ham-like, sweet, salty taste and an elastic texture which are flavored by the panelists. The storage life of smoked sailfish packed in styropore trays covered with saran clingfilm at 0°C. 14°C and 35°C was determined. Results of the storage study showed that the product is stable at 0°C. At chilled temperature, it was found to be acceptable until the 29th day. Products stored at ambient temperature had a shelflife of 5-6 days. The amount of total volatile bases proved to be a reliable quality index during storage at ambient temperature. A decrease in freshness of odor and flavor also occurred at the said temperature as storage time progressed. Thus, storage of smoked sailfish at low temperature can extend the shelf-life of the product.